HUBUNGAN ANTARA ALIENASI DENGAN KETERAMPILAN KOMUNIKASI INTERPERSONAL PADA MAHASISWA UNIVERSITAS NEGERI PADANG - Putra, Deri Sakri; Zulian Fikry (Causalita, 2024)
Alienation is a condition or condition of a person who is separated or alienated from other people, the surrounding environment, and even himself. One of the factors causing alienation in students is less effective interpersonal communication skills. This research aims to determine the relationship between alienation and interpersonal communication skills in Padang State University students. The research design used in this research is quantitative research. The population in this study were Padang State University students. The sampling technique used was the Accidental Sampling technique with a sample size of 202 people. The measuring instrument in this research uses a scale of alienation and interpersonal communication skills with reliability values ​​of 0.924 and 0.845. The data analysis technique used in this research is Pearson Product Moment correlation analysis. The results of this study show that there is a negative relationship between alienation and interpersonal communication skills in Padang State University students with a value of p=0.000 (p<0.05). From the research results it can be concluded that Ha is accepted and Ho is rejected.